The Role of Nahdlatul Ulama and Muhammadiyah Youth in Promoting Islamic Moderation in Indonesia - Mukhsin, Mukhsin; Hubby Dzikrillah Alfani, Ilzam; Fauzi, Ridwan (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
Youth play a vital role as agents of change in promoting religious moderation values. In Indonesia, this role is strategic and contributive, given the significant potential that youth possess, such as energy, creativity, and broad access to education and information. Youth also have the ability to create interfaith dialogue and actively engage in public policy. This study aims to analyze the contributions of youth from Nahdlatul Ulama and Muhammadiyah, which have the power to influence social change, particularly in the religious context, by promoting values of tolerance, harmony, and unity, preventing radicalism, and fostering interfaith cooperation. To achieve this, the study employs a qualitative approach, relying on literature review and descriptive-analytical data analysis. This research concludes that, despite their great potential, youth face challenges such as the influence of radicalization, social stigma, lack of education on moderation, and environmental and cultural pressures. Other barriers include the negative influence of social media, cultural resistance, lack of institutional support, and limited access and resources. To address these challenges, specific strategies are needed, such as the development of moderation-based training programs, as well as youth involvement in community activities. Additionally, government support through policies, funding, and facilities is also a crucial factor. Through education, social media, and community activities, youth can harness their potential to promote Islamic moderation, creating a more tolerant, inclusive, and harmonious society amidst diversity.Abstrak: Pemuda memegang peran vital sebagai agen perubahan dalam mempromosikan nilai-nilai moderasi beragama. Di Indonesia, peran ini bersifat strategis dan kontributif mengingat potensi besar yang dimiliki pemuda seperti energi, kreativitas, serta akses luas terhadap pendidikan dan informasi. Pemuda juga memiliki kemampuan menciptakan dialog lintas agama dan keterlibatan aktif dalam kebijakan publik. Penelitian ini bertujuan menganalisis kontribusi pemuda Nahdlatul Ulama dan Muhammadiyah memiliki kekuatan untuk memengaruhi perubahan sosial, terutama dalam konteks keagamaan, dengan mempromosikan nilai-nilai toleransi, harmoni, dan persatuan, mencegah radikalisme, dan membangun kerja sama lintas agama. Untuk mencapai tujuan tersebut, penelitian ini menggunakan pendekatan kualitatif dengan mengandalkan kajian pustaka dan data dianalisis secara deskriptif-analitis. Penelitian ini menyimpulkan bahwa meski memiliki potensi besar, pemuda menghadapi tantangan seperti pengaruh radikalisasi, stigma sosial, kurangnya pendidikan tentang moderasi, serta tekanan lingkungan dan budaya. Hambatan lain termasuk pengaruh negatif media sosial, resistensi budaya, kurangnya dukungan institusi, serta keterbatasan akses dan sumber daya. Untuk mengatasi tantangan ini, diperlukan strategi khusus, seperti pengembangan program pelatihan, pendidikan berbasis moderasi, serta pelibatan pemuda dalam kegiatan komunitas. Selain itu, dukungan pemerintah melalui kebijakan, pendanaan, dan fasilitas juga menjadi faktor penting. Melalui pendidikan, media sosial, dan kegiatan komunitas, pemuda dapat memanfaatkan potensi mereka untuk mempromosikan moderasi Islam, menciptakan masyarakat yang lebih toleran, inklusif, dan harmonis di tengah keberagaman.